A radical sense of direction: Signalling and mechanism in cryptochrome magnetoreception - Dodson, C; Hore, P; Wallace, M (2013)
The remarkable phenomenon of magnetoreception in migratory birds and other organisms has fascinated biologists for decades. Much evidence has accumulated to suggest that birds sense the magnetic field of the Earth using photochemical transformations in cryptochrome flavoproteins. In the last 5 years this highly interdisciplinary field has seen advances in structural biology, biophysics, spin chemistry, and genetic studies in model organisms. We review these developments and consider how this chemical signal can be integrated into the cellular response. © 2013 Elsevier Ltd.